Economic Sociology Review of Car Pawn Practices in Pinrang Regency - Nurjannah, Nurjannah; Bahri, Andi; Mahsyar, Mahsyar; Semaun, Syahriyah; Musyarif, Musyarif (Universitas Tanjungpura, 2024)
This thesis delves into the Economic Sociology Review of Car Pawn Practices in Pinrang Regency. The study aims to explore the practice of car pawning, factors influencing people's decision to pawn their cars, and the economic sociology perspective on car pawning. The research adopts a qualitative approach, specifically phenomenology. Data collection techniques include interviews, observations, and documentation, with data validity assessed through credibility, transferability, dependability, and confirmability. Key findings of the study include: 1) Car pawning practices are prevalent in Lanrisang and Siparappe neighborhoods in Pinrang Regency, with pawnshops operating without registration with the Financial Services Authority. The assessment of collateral is conducted by the pawnbroker, impacting the loan amount and monthly interest rates. Transactions are documented through receipt slips, and if the loan defaults, ownership of the collateral is transferred or sold by the pawnbroker. 2) People opt for car pawning due to its lenient requirements, non-restrictive operating hours, and minimal conditions for loan approval. 3) Economic actions in the context of economic sociology are characterized as irrational actions influenced by motives, interests, experiences, and expectations. These actions fall into the categories of affective and traditional actions. Keywords: Economic Sociology, Car Pawn